REMNANTS OF OTTOMAN LAW AND ITS APPLICATION IN CONTEMPORARY TIMES IN LEBANON AND THE ARAB WORLD - Kamaluddin, Safrudin Halimiy (Jurnal AL-AHKAM, 2021)
At the beginning of the sixteenth century (1516), the Ottomans controlled all the lands that are today within the Lebanese Republic, and their existence lasted for four hundred  years,  during which  they established  military,  security, administrative and social systems and enacted laws to improve and organize the country. Although five centuries have passed since the Ottoman presence in Lebanon, some of these laws are still in force. Some have been amended, such as the personal status law related to Islamic Law, some administrative regulations, and the municipal ordinance that the French updated during the Mandate days (1920-1943). While Ottoman laws are still strictly enforced in Lebanon, such as the Associations Law. Two sources, one legal and the other specialized in Islamic history, confirm in two separate interviews to Anadolu Agency the importance of these laws for Lebanon since their enactment until today. "Not everything old is considered  bad.  For  example,  but  not  limited to,  the Associations  Law is  an Ottoman law that enshrines freedom of association and respects Article 13 of the Constitution,  and  despite  its  promulgation  in  1909,  it  has  been  considered  a liberal law to date," says Appeals Lawyer Zakaria Yahya beast. Al-Ghoul added: "The Law of Associations is one of the most important laws issued during the Ottoman period. It is still in force to date, and it is the one who looks after the affairs of associations and how they are formed in Lebanon and the Arabs World. He  pointed  out  that  "there  is  a  legislative  decree  issued  in  1977,  which  is compared to the Ottoman Law of Associations as a recent law, but it allowed the pre-trial detention of  journalists." He continued, "From here, this comparison makes us say that the problem does not lie in the extent of the laws' antiquity, but rather in the extent to which they meet the objectives of the current legal rules."